2005
DOI: 10.1017/s0950268805005017
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife rabies in Western Turkey: the spread of rabies through the western provinces of Turkey

Abstract: The incidence of rabies has decreased in Turkey during recent years. However, an increasing number of rabies cases have been reported in the Aegean (western) region of Turkey. The virus appears to have maintained a foothold in the urban areas of the province of Izmir with only three cases per year being reported during the mid-1990s. Since 2001, the virus has been recorded in the previously rabies-free provinces of Manisa and Aydin. During this epizootic, cases have been reported in both dogs and foxes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
1
19
0
3
Order By: Relevance
“…[8][9][10] Negativity in tests was first detected in the corneal smear samples with FAT when all complaints and general status of the patient fully improved. When his saliva was negative with RT-PCR method repeated after 14 days, he was discharged from the hospital with full recovery on the 66 th day of his hospitalization.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Negativity in tests was first detected in the corneal smear samples with FAT when all complaints and general status of the patient fully improved. When his saliva was negative with RT-PCR method repeated after 14 days, he was discharged from the hospital with full recovery on the 66 th day of his hospitalization.…”
Section: Case Reportmentioning
confidence: 99%
“…Similarity between the sequence analyses of viral RNA obtained by PCR method in our case and the sequence analyses of rabies virus species previously encountered in Eastern Anatolian Region of our country. [8][9][10] There is no established, specific treatment for rabies once symptoms of encephalitis begin. Despite excellent intensive care, almost all patients succumb to the disease or its complications, within a few weeks of onset.…”
mentioning
confidence: 99%
“…Occasional cases of rabies have always been reported in the red fox (Vulpes vulpes). Careful mapping of the appearance of fox cases [15] has suggested that there was spread of the disease from a site to the west of the city of Izmir in 1999, eastwards into the province of Manisa and south into the province of Aydin (Fig. 2 d) and appears to be associated with an increase in the number of domestic animals infected with rabies, now in excess of the number of dog cases.…”
Section: Rabies In Wildlifementioning
confidence: 99%
“…This prompted further investigation of rabies virus isolates from within Turkey with the result that two major populations were identified (Fig. However, in recent years the western clade has spread south and east entering provinces that had previously been free of the disease such as Aydin, Manisa, Mugla and Denizli [15]. These are a western clade composed of groups recovered from the urban centres of Istanbul, Bursa and Izmir, and an eastern clade composed of disparate isolates found throughout the eastern provinces of Turkey [21].…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Although rabies prevalence appears to be in gradual decline, it could be that residual foci may still persist in some isolated areas and could potentially serve as sources of subsequent outbreaks in the presence of susceptible dog populations [13].…”
mentioning
confidence: 99%